47.5k views
0 votes
(3x+7)(2x-5) using the FOIL method, Multiply the terms in the binomial

1 Answer

4 votes

Answer:

6x^2 - x - 35

Explanation:

So the FOIL method can be described as "First, Outer, Inner, Last"

First: 3x * 2x = 6x^2

Outer: 3x * -5 = -15x

Inner: 2x * 7 = 14x

Last: 7 * -5 = -35

Then, you simply add all of these terms together:

6x^2 - 15x + 14x - 35

Then simplify:

6x^2 - x - 35

User Cristian Guaman
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.